Some thoughts about misconceptions surrounding the term 'biofilm'. (16th November 2020) - Javaherdashti, Reza
ABSTRACT: The central concept of microbiologically influenced corrosion is 'biofilm'. However, it is neither a 100% biological fabric nor a film. While biofilms though mechanisms such as establishment of differential aeration cells can accelerate corrosion, under certain circumstances such as thickening may also decelerate corrosion. In this article, these mechanisms will be discussed. Along with that, this author also introduces a new term that can replace the term 'biofilm'. This new term, 'temenos', has been proposed to indicate that when a biofilm forms, electrochemical conditions under the biofilm and those of the bulk will be highly different from each other.